Potassium Mobilization and Transformation in Red Paddy Soil as Affected by Rice. (1st May 2014) - Li, Xiaokun; Zhan, Liping; Lu, Jianwei; Liao, Zhiwen; Li, Jifu; Ren, Tao; Cong, Rihuan
Abstract : A rhizobox experiment was conducted to study the effect of growing rice ( Oryza sativa L.) on the movement and transformation of K in a red paddy soil. Results showed that K uptake by rice reduced the concentrations of soil water‐soluble K (Sol‐K), exchangeable K (Ex‐K), and non‐exchangeable K (Nonex‐K) in the root zone. Soil Sol‐K in non‐root‐zone compartment close to the root zone (0–6 cm) migrated toward the root zone, and soil Ex‐K (0–4 cm) and soil Nonex‐K (0–3 cm) was released into soil solution. As the rice growth progressed, soil Sol‐K, Ex‐K, and Nonex‐K in the root zone and soil Sol‐K in non‐root‐zone compartment close to the root zone (0–6 cm) continued to decrease. Decreases of soil Ex‐K and Nonex‐K in non‐root‐zone compartment extended from the root to 6 and 5 cm into the bulk soil, respectively. At the late grain‐filling stage, soil Sol‐K concentration in the root zone and non‐root‐zone compartment (0–6 cm) declined, and then remained stable, whereas Sol‐K in the non‐root zone (6–7 cm) kept diffusing toward the root zone. Soil Ex‐K and Nonex‐K in the root zone and non‐root‐zone compartment continued to reduce, and the decrease distance of soil Nonex‐K was extended to 6 cm. Within the whole season, soil Ex‐K and Nonex‐K were the main forms of K available to the plants, followed by Sol‐K. The information obtained in this study indicated that K fertilizer should be added to the place around the root zone.